International Reserves, External Debt Maturity, and the Reinforcement Effect for Financial Stability - Xingwang Qian; Andreas Steiner (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
This paper studies how the maturity structure of external debt is affected by internationalreserves and how they reinforce financial stability through a more crisis-resilientmaturity structure. We show in an illustrative theoretical model that reserves lengthenthe maturity of external debt via a flattening of the yield curve. Using data of 66 emergingand developing countries and applying different econometric approaches, we find robustevidence that reserves increase the share of long-term (LT) relative to short-term (ST)external debt. Results hold for private and public external debt individually. Takingreserves and their effect on the debt maturity structure together, they reinforce financialstability.
Keywords: F30; F40; 330; International reserves; capital inflows; debt maturity